Prospective evaluation of patient-reported outcomes of invisible ink tattoos for the delivery of external beam radiation therapy: the PREFER trial - Hardy-Abeloos, Camille; Gorovets, Daniel; Lewis, Aurora; Ji, Wenyan; Lozano, Alicia; Tung, Chih Chun; Yu, Francis; Hanlon, Alexandra; Lin, Haibo; Kha, Anh; Yamada, Yoshiya; Kabarriti, Rafi; et al. (Frontiers in Oncology, 2024)
Introduction: Invisible ink tattoos (IITs) avoid cosmetic permanence of visible ink tattoos (VITs) while serving as more reliable landmarks for radiation setup than tattooless setups. This trial evaluated patient-reported preference and feasibility of IIT implementation.In an IRB-approved, single institution, prospective trial, patients receiving proton therapy underwent IIT-based treatment setup. A survey tool assessed patient preference on tattoos using a Likert scale. Matched patients treated using our institutional standard tattooless setup were identified; treatment times and image guidance requirements were evaluated between tattooless and IIT-based alignment approaches. Distribution differences were estimated using Wilcoxon ranksum tests or Chi-square tests.Results: Of 94 eligible patients enrolled, median age was 58 years, and 58.5% were female. Most common treatment sites were breast (18.1%), lung (17.0%) and pelvic (14.9%). Patients preferred to receive IITs versus VITs (79.8% pre-treatment and 75.5% post-treatment, respectively). Patients were willing to travel farther from home to avoid VITs versus IITs (p<0.01). Females were willing to travel (45.5% vs. 23.1%; p=0.04) and pay additional money to avoid VITs (34.5% vs. 5.1%; p<0.01). Per-fraction average +treatment time and time from on table/in room to first beam were shorter with IIT-based vs. tattooless setup (12.3min vs. 14.1min; p=0.04 and 24.1min vs. 26.2min; p=0.02, respectively).Discussion: In the largest prospective trial on IIT-based radiotherapy setup to date, we found that patients prefer IITs to VITs. Additionally, IIT-based alignment is an effective and efficient strategy in comparison with tattooless setup. Standard incorporation of IITs for patient setup should be strongly considered.*P-values were calculated based on Wilcoxon rank-sum tests; IQR: Interquartile Range.